2018
DOI: 10.1038/s41467-018-03864-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of two-dimensional excitons in monolayer WSe2

Abstract: Two-dimensional (2D) semiconducting materials are promising building blocks for optoelectronic applications, many of which require efficient dissociation of excitons into free electrons and holes. However, the strongly bound excitons arising from the enhanced Coulomb interaction in these monolayers suppresses the creation of free carriers. Here, we identify the main exciton dissociation mechanism through time and spectrally resolved photocurrent measurements in a monolayer WSe2 p–n junction. We find that under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
189
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 154 publications
(211 citation statements)
references
References 49 publications
18
189
2
2
Order By: Relevance
“…That work also showed that the photocurrent generated in fields weaker than 15 V/µm was accurately predicted by the Mott-Wannier model [16,17]. Nevertheless, these weakfield dissociation rates proved troublesome to obtain numerically [15], and they were therefore extrapolated by fitting to the rate of a two-dimensional hydrogen atom [18]. In the present paper, we introduce a numerical method capable of computing exciton dissociation rates for significantly weaker fields with no compromise on the accuracy for stronger fields.…”
Section: Introductionmentioning
confidence: 93%
“…That work also showed that the photocurrent generated in fields weaker than 15 V/µm was accurately predicted by the Mott-Wannier model [16,17]. Nevertheless, these weakfield dissociation rates proved troublesome to obtain numerically [15], and they were therefore extrapolated by fitting to the rate of a two-dimensional hydrogen atom [18]. In the present paper, we introduce a numerical method capable of computing exciton dissociation rates for significantly weaker fields with no compromise on the accuracy for stronger fields.…”
Section: Introductionmentioning
confidence: 93%
“…When the exciton is subjected to an electrostatic field, it may be dissociated. This is realized in the Wannier model by the energy eigenvalue obtaining a non-vanishing imaginary part [27][28][29]68 . The field induced dissociation rate is then given by Γ = −2 Im E, where the imaginary part can be obtained efficiently by utilizing the ECS technique [51][52][53][54] .…”
Section: Field Induced Dissociationmentioning
confidence: 99%
“…Without inducing dissociation in some way, excitons will typically recombine before they are dissociated. Applying an in-plane electric field to the excitons, however, enhances generation of photocurrents for two reasons: (i) the electric field counteracts recombination by pulling electrons and holes in opposite directions, and (ii) the electric field assists dissociation of excitons [27][28][29][30] .When two TMD monolayers are brought together with a type-II band alignment, the conduction band minimum and the valence band maximum reside in two different layers. Electrons and holes in the structure will therefore prefer to reside in separate layers, provided that the loss in exciton binding energy is smaller than the energy gained by band offsets.…”
mentioning
confidence: 99%
“…2 To date, the properties of free neutral excitons and exciton complexes such as charged excitons (trions) have been studied and largely understood 3,4 . Binding energies [5][6][7] , formation and dissociation mechanisms 8,9 , coherence effects 10 , and spin-valley effects [11][12][13][14][15][16][17] of these excitons have been identified. In addition to neutral and charged excitonic peaks, a feature that is often attributed to localized, rather than free excitons appears in photoluminescence (PL) spectra of many TMDC devices at low temperatures [18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%